The Influence of Product Quality, Price and Brand on the Decision Purchase Hand Sanitizer in Semarang - R.A, marlien; Cahyo Wibowo Jati; Andreas Tigor Oktaga (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Abstract The purchasing decision is the stage in the buyer’s decision-making process where consumers actually buy. The purchase of products, services, ideas, or experiences that satisfy the needs and desires of individuals, groups, and organizations to make choices, purchases, and uses. So that purchasing decisions form attitudes in consumers to process all information and draw conclusions in the form of responses that emerge as to what product to buy. The purpose of this research is to find out how product quality, price and brand influence purchasing decisions? This research chose the object Lifebuoy hand sanitizer. The research sampling technique used purposive sampling. The findings are that product quality, price and brand have a positive effect on purchasing decisions. Keywords: product, price, brand, purchase decision